Know your history. know it well - Abd Razak, Dzulkifli (2009)
MALAYSIA will celebrate its 52nd year of Merdeka tomorrow, and it is timely to reflect on what has happened since the nation gained independence in 1957. Amidst the joy and fanfare, there must be a serious revisit to the history of the events that led to this annual celebration. They say, history is a great teacher. But unless this is done in earnest, Merdeka tends to have a repetitive dampening effect in which the context is largely lost. It will be reduced to a onetime cyclical happening, devoid of any meaning.